2017
DOI: 10.18639/rabm.2017.03.456895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spirituality and Religion on Adherence to Highly Active Antiretroviral Therapy in Adult HIV/AIDS Patients in Calabar, Nigeria

Abstract: The emergence of a chronic medical illness such as Human Immune Deficiency Virus and Acquired Immunodeficiency Syndrome (HIV/AIDS) may be the time when people turn to the Sacred through spirituality and religion. HIV is a chronic illness that requires strict adherence to medication regimens that may be influenced by spirituality/religion. This study was aimed at finding the association between spirituality/religion and adherence to highly active antiretroviral therapy (HAART) in adult HIV/AIDS patients. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Therefore, spiritual health can enhance the level of health behaviors, reinforcing effects on physical status, patient's compatibility with the disease, and follow-up of the treatment process [28]. A previous research explored the effects of spirituality and religion on the adherence to antiretroviral therapy among adult HIV patients and came to the conclusion that both spirituality and positive religious coping could have positive impacts on desirable adherence to the treatment regimen [29]. The results of another study indicated that the mothers with children suffering from cystic fibrosis who believed in God and considered their children's bodies as the manifestation of the presence of God were more determined to adhere to their children's treatment measures and drugs consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spiritual health can enhance the level of health behaviors, reinforcing effects on physical status, patient's compatibility with the disease, and follow-up of the treatment process [28]. A previous research explored the effects of spirituality and religion on the adherence to antiretroviral therapy among adult HIV patients and came to the conclusion that both spirituality and positive religious coping could have positive impacts on desirable adherence to the treatment regimen [29]. The results of another study indicated that the mothers with children suffering from cystic fibrosis who believed in God and considered their children's bodies as the manifestation of the presence of God were more determined to adhere to their children's treatment measures and drugs consumption.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with previous studies conducted in Nigeria, South Africa, Canada, and the United States of America which reported significant gender differences in the sociodemographic characteristics of respondents in favour of the male group compared to their female counterparts. 14,[28][29][30][31][32] This suggests that sociodemographic variables like; age, marital status, tribe, religion, place of residence, level of education, and occupation may influence adherence to ART and the virologic outcome of PLWHA.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies conducted in Nigeria, South Africa, Tanzania, Canada, and the United States of America which showed statistically significant gender disparities in the socio-demographic characteristics of HIV-positive respondents. 18,[34][35][36][37][38][39] Conversely, a systematic review carried out in sub-Saharan Africa in addition to other crosssectional studies conducted in the Gambia and South Africa reported higher odds of self-reported optimal adherence among the female respondents compared to their male counterparts. 29,31,40 However, there was no observed statistically significant gender difference between self-reported adherence and socio-demographic variables in studies conducted in Togo, Cameroun, Malawi and the United States of America.…”
Section: Discussionmentioning
confidence: 99%